Grain-size, coarse fraction lithology and clay mineral compositions of surface sediments from Ross Sea, Antarctica: implications for their provenance and delivery mode - Wu, Li; Li, Longwei; Wang, Rujian; Shao, Hebin; Chen, Yi; Lin, Zipei; Liu, Yue; Xiao, Wenshen; Xu, Ran (Frontiers in Marine Science, 2024)
Knowledge on spatial distribution, provenance and delivery mode of surface sediment aids in interpretation of nearby sediment records for paleoenvironmental reconstruction. Such knowledge, however, remains largely unknown for the modern Ross Sea, Antarctica: a key region for understanding the dynamical behavior of Antarctic Ice Sheet over geological past. In this study, we address this gap by analyzing the grain-size distribution, coarse fraction (>250 μm) lithology, and clay mineralogy of a set of surface sediment samples covering the whole Ross Sea continental shelf. Our data reveals that the sediments were mostly delivered by icebergs and bottom currents. Iceberg delivery was significantly controlled by factors such as water depth, proximity to the iceberg sources, and invasion of the Modified Circumpolar Deep Water. Bottom current activity was stronger in the Western Ross Sea (WRS) than in the Eastern Ross Sea (ERS), controlled by the formation and transport of Dense Shelf Water. Three major sorts of coarse fraction were identified, including the quartz-rich Iceberg Rafted Detritus (IRD) originating from West Antarctic glaciers and primarily distributed in the ERS, the mafic rocks-rich IRD from the Ferrar Group as well as the McMurdo Volcanic Group and mainly found in the WRS, and deformed silt traced back to the grounding zone of the David Glacier-Dragalski Ice Tongue system. The distribution of clay minerals is dominated by a distinct binary mixing pattern.Smectite and kaolinite are mainly present in the ERS, derived from beneath the West Antarctic Ice Sheet. Higher illite and chlorite contents were found offshore of the Southern Victoria Land, derived from the East Antarctic craton.Overall, these results demonstrate that the glaciers draining into Ross Sea from both the East and West Antarctic Ice Sheets are highly dynamical in the context of modern climate conditions, with implications for potential contribution to future sea level rise.